PELATIHAN WEB DESIGN PROGRAM STUDI SEBAGAI MEDIA SOSIALISASI DAN PROMOSI DIGITAL - Masud, Abdu; Ahmad, Zulkifli; Sundari, Sundari (-, 2025)
Issues regarding the number of students in study programs are often the main focus for universities, which are not only limited to recruiting new students, but are related to the retention of existing students in certain study programs. Socialization and promotion of study programs using digital-based strategies is an effective approach to reaching prospective students in the current digital era. Service activities are carried out through 6 stages, namely conducting needs analysis, digital platform design, development stage, socialization, feedback, and monitoring and evaluation. The results of the needs analysis show that the study program web admin needs to be assisted and upgrade his website design skills so that the study program website becomes better in terms of layout so that it can attract the interest of new students. This training activity is very beneficial for study programs within the scope of FKIP, as well as providing access for prospective new students to information related to the target study program. The results of this training have an impact on the study program web admin's skills regarding WordPress dashboard management and technical input of news (information) on the study program website.